The effect of rehabilitation procedures used during training on the state of the autonomic nervous system in professional basketball players - Andreev D.S.; Konovalov I.E.; Parfenova L.A.; Andreev V.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study. This study is aimed at analyzing the dynamics of the vegetative state in professional basketball players, depending on the use of various recovery methods in the training process. Methods and structure of the study. The study was conducted on the basis of the Volga State University of Physical Culture, Sports and Tourism with the participation of 30 qualified basketball players. The vegetative status was assessed by analyzing the coefficient of vegetative tone, reflecting the balance of the sympathetic and parasympathetic nervous systems. Results and conclusions. The results showed that at the beginning of the study, athletes in both groups showed signs of compensated fatigue, which may negatively affect the effectiveness of training at the beginning of the season. By the end of the study, in the experimental group where restorative measures were used, an improvement in the indicators of vegetative status to the level of optimal working capacity was noted, indicating that the load was adequate to the capabilities of athletes. In the control group, where no recovery measures were carried out, the indicators remained at the same level, which can lead to a cumulative effect of fatigue and a decrease in the effectiveness of the game by the end of the season. The data obtained indicate that the improvement of the vegetative coefficient is possible only with the systematic use of restorative measures in the training process.